2008
DOI: 10.1002/ijc.23635
|View full text |Cite
|
Sign up to set email alerts
|

Ku70 predicts response and primary tumor recurrence after therapy in locally advanced head and neck cancer

Abstract: Abstract5‐Fluorouracil and cisplatin‐based induction chemotherapy (IC) is commonly used to treat locally advanced head and neck squamous cell carcinoma (HNSCC). The role of nonhomologous end joining (NHEJ) genes (Ku70, Ku80 and DNA‐PKcs) in double‐strand break (DSB) repair, genomic instability and apoptosis suggest a possible impact on tumor response to radiotherapy, 5‐fluorouracil or cisplatin, as these agents are direct or indirect inductors of DSBs. We evaluated the relationship between Ku80, Ku70 or DNA PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 66 publications
(79 reference statements)
2
21
0
Order By: Relevance
“…No significant association was found between the level of RAD50 expression and clinical outcome. These results suggest that the response to DNA damage involving the NHEJ system could be dependent to the types of cancer cells (Pavon et al, 2008). Another possible explanation is that LIG4 may have other functions besides repairing DSB, like the DSB recognition of Nbs1.…”
Section: Discussionmentioning
confidence: 90%
“…No significant association was found between the level of RAD50 expression and clinical outcome. These results suggest that the response to DNA damage involving the NHEJ system could be dependent to the types of cancer cells (Pavon et al, 2008). Another possible explanation is that LIG4 may have other functions besides repairing DSB, like the DSB recognition of Nbs1.…”
Section: Discussionmentioning
confidence: 90%
“…The lysates from two 96-well plates were collected into the same microcentrifuge tube and then processed according to the manufacturer's protocol. Reverse transcription was done with the High Capacity cDNA Archive kit (Applied Biosystems Incorp), and mRNA expression was determined using an ABIPrism 7000 Sequence Detection System (Applied Biosystems) as described (15). Predesigned Taqman Gene Expression Primer and Probe assays (Applied Biosystems) were available for human cathepsin B (HS00157194_m1) and the housekeeping gene hypoxanthine phosphoribosyltransferase 1 (HS99999909_m1; endogenous control).…”
Section: Methodsmentioning
confidence: 99%
“…Cancer Res 2008; 68: (15 finding in caspase-dependent and caspase-independent pancreatic carcinoma cell death induced by Bobel-24 or its derivatives, as we have previously described in caspase-independent cell death in leukemic cells (6). Consequently, we explored whether pancreatic carcinoma cell death by Bobel-24 or Bobel-16 was mediated by cytochrome c release (common in caspase-dependent death) and/ or mitochondrial release and nuclear translocation of AIF (common in caspase-independent death).…”
Section: Cancer Researchmentioning
confidence: 99%
“…A pre and post-treatment trial demonstrated that nuclear PARP1 overexpression in oral cancer is inducible following radiotherapy, however overall intensity is not predictive of treatment effectiveness or prognosis [235]. A larger non-subsite specific HNSCC study also showed an exclusively nuclear staining pattern, and while this demonstrated a higher disease-free survival with high Ku70 expression this was a cross-site analysis with only 22% from the oral cavity [105]. A strong nuclear expression pattern for Ku70 was noted in colorectal carcinoma, with 20% of carcinoma and 55% of adenoma showing cytoplasmic staining [236].…”
Section: Section 504 Methodology Discussionmentioning
confidence: 99%
“…While this study did not include tongue cancer specimens, the predictive value was greatest in HPV negative cancers (RR 9, P <0.01). In contrast, two similarly-sized mixed studies found Ku70 mRNA levels and protein overexpression improved recurrence-free survival in locally-advanced HNSCC [105] and tonsillar cancer [157], however these did not stratify for p16 status and had unusual treatment regimens. In support of these findings are in-vitro studies showing that Ku70 loss improved radioresistance in late G2/S, possibly by allowing the more error-free HR [145].…”
mentioning
confidence: 84%